Elecrical Tomography and VLF methods contribution to underground wastewater pipe construction - Vargemezis, G.; Gerolymatos, E.; Aggelopoulos, A. (Bulletin of the Geological Society of Greece, 2007)
In the area of municipality ofKropia (Attica, Athens) the construction of a tunnel for the transportation of treated wastewater has been decided. The length of the tunnel is approximately 1400 m and it is designed to cross an area at a depth of maximum 100 meters. Geological and tectonic mapping showed the existence of limestone and fault systems zones that are crossing the geological formations. Thus, geophysical survey has been designed in order to provide information about the geological and tectonic status at the proposed area. The application of electrical tomography has been designed in addition with VLF electromagnetic method. The first one was expected to show the geological cross section at the axis designed while the VLF method could provide more detailed information about the fault structures zones at the area. Results of the geophysical survey showed lateral changes of the mechanical behavior of the limestone. In parallel, fault zones that are crossing the axis have been mapped. Considering that engineers need to know the nature of probable problems that they have to deal with, geophysical investigation can provide useful information in a low cost and quick application and contribute to the best decision as concern the final positioning of the tunnel and the penetrating method.